Latent autoimmune diabetes in youth - Sun, Qingxia; Yang, Min; Jing, Yiheng; Meng, Lingzhe; Zhang, Chang; Ruan, Jie; Wu, Na (Frontiers in Immunology, 2025)
Latent autoimmune diabetes in youth (LADY) is an emerging and under-recognized subtype of autoimmune diabetes, occurring in young individuals who present with clinical features overlapping both type 1 and type 2 diabetes. LADY shares pathophysiological characteristics with latent autoimmune diabetes in adults (LADA) yet differs in its earlier onset and stronger autoimmune response. Due to its heterogeneous presentation, LADY is frequently misclassified as type 2 diabetes in youth, leading to delays in appropriate treatment. Moreover, there are currently no universally accepted diagnostic criteria or screening strategies specific to LADY. As a result, clinical management remains inconsistent and controversial. Given the rising incidence of autoimmune diabetes in youth and the clinical consequences of delayed diagnosis, there is an urgent need to better characterize LADY and develop age-specific diagnostic and therapeutic approaches. In this review, we summarize the current knowledge regarding the epidemiology, pathogenesis, clinical features, diagnostic challenges, and treatment strategies of LADY. We also highlight the existing knowledge gaps and propose directions for future research and clinical practice with the aim of improving the recognition and management of this unique diabetes subtype in the pediatric population.